OP56 Increasing rates of self-harm among children, adolescents and young adults: a ten-year national registry study 2007–2016. (3rd September 2019) - Griffin, E; McMahon, E; McNicholas, F; Corcoran, P; Perry, IJ; Arensman, E
Abstract : Background: Self-harm is a significant public health issue with highest rates recorded among young people. Few studies have examined recent trends in self-harm across children, adolescents and young adults. The current study examined trends in rates and methods of self-harm among young people in Ireland over a ten-year period. Methods: Data from the National Self-Harm Registry Ireland on presentations to hospital emergency departments (EDs) following self-harm by those aged 10–24 years during the period 2007–2016 were included. We calculated annual self-harm rates per 100, 000 by age, gender and method of self-harm. Poisson Regression models were used to examine trends in rates of self-harm. Results: The average person-based rate of self-harm among 10–24 year-olds was 318 per 100, 000. Peak rates were observed among 15–19 year-old females (564 per 100, 000) and 20–24 year-old males (448 per 100, 000). Over a ten-year period, rates of self-harm increased by 22% overall (IRR=1.22, 95% CI=1.16–1.29), with increases most pronounced for females. Among 10–14 year-olds, the self-harm rate increased by 75% (IRR=1.75, 95% CI=1.15–2.10), with a 25% increase for 15–19 year-olds (IRR=1.25, 95% CI=1.16–1.35) and a 39% increase among 20–24 year-olds (IRR=1.39, 95% CI=1.29–1.50). There were marked increases in specific methods of self-harm, including those associated with high lethality such as self-cutting and attempted hanging. Conclusion: Increases in rates of self-harm were recorded across all age groups of children, adolescents and young adults over the ten year study period and our findings indicate that the age of onset of self-harm is decreasing. These increasing rates have been accompanied by large increases in the use of highly lethal methods. Further examination of these trends is needed to identify mental health service needs and deficits for young people in the key transition stages between childhood and adolescence and adolescence and adulthood.